TUGAS DAN WEWENANG KEJAKSAAN DALAM PELAKSANAAN PEMILIHAN UMUM - M. Yuhdi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2014)
Judiciary including district attorneys, state attorneys, and state attorney branches have duties and obligations on the election administration. The duties of a district attorney chief are collecting data and information; receiving reports; processing and analyzing data and information he gets by himself and from state attorney’s reports; making and submitting reports to the chair person; giving technical instructions to the chiefs of state attorneys in his law area; having coordination and synchronization with the regional intelligence community and with other related parties. Then, the duties of the state attorney chief are collecting data and information dealing with generalelections; receiving reports from state attorney branches (if has branches); processing and analyzing data and information he gets by himself and from the branches’ reports; having coordination and synchronization with the regional intelligence community and with other related parties. The chief of state attorney brand has the same duties as the chief of state attorney. Finally, the reports are submitted to the district attorney.